Study of the Experimental Conditions of the Co-pyrolysis of Rice Husk and Plastic Wastes - P. Costa; F. Pinto; M. Miranda; R.N. André; M. Rodrigues (Chemical Engineering Transactions, 2014)
The main objective of this study is to access the technical and economical viability of using pyrolysis technology applied to the rice production main wastes to produce bio-fuels to substitute fossil fuels and electricity consumption during rice milling processes. Therefore, it was studied the effect of operating conditions (reaction temperature, initial pressure and reaction time) on products yields and quality, as well as the possible synergetic effects that may occur during the pyrolysis of these wastes. The pyrolysis experiments were performed in 1 L capacity batch reactor made of Hastelloy C276 and built by Parr Instruments. According to previous studies, the range of operational conditions studied was: 350-430 ºC for reaction temperature, 2-10 bar for initial pressure and 10-60 min for reaction time. So far, the results obtained showed that these two wastes can be processed together. The presence of PE seems to favour the biomass conversion, as PE is easily converted into liquids by pyrolysis, which increases heat and mass transfer in the reaction medium.